Ukrainian education in European educational context - Ponomariov, A.; Cheremsky, M. (New Collegium, 2023)
The integration of Ukrainian education into the European educational space is main theme of this article. The differences between the Ukrainian and European education systems are considered. The ways of involving European and other Western forms and methods of education and personality education in Ukrainian schools are determined. These forms and methods have a creative basis. They are activating the thoughts, feelings and imagination of personality. Western pedagogy is distinguished by its democracy and humanism. This pedagogy are educating a free, comprehensively developed, creative, competitive personality. Thanks to the freedom the pupil and student have the opportunity to develop in accordance with their peculiarities and capabilities. Children may or may not prepare homework. The pupil himself decides whether he needs to do homework at home. The students independently determine the task and date for presentation this task. Because in Western education, in contrast to our education, there is individual approach to personality. The Dalton-plan is playing an important role in determining the individual peculiarities of personality. European pedagogy is art. Art is facilitating the learning for pupils and students. Art is developing creative abilities of personality. Therefore teacher must be creative personality. Very important art method for learning is play. Thanks to play children are learning with great enthusiasm. Our education practically does not use play method of learning. But for a child the play is the main method of learning. By means play pupil develops his own physical and spiritual powers. The play contributes to the development of the child's social sense. The involvement of creative methods of learning will contribute to the humanization, democratization and European integration of Ukrainian education.